Smart PTFE Membrane with Hydrophilicity and pH Sensitivity through MAA-grafting. Issue 1 (2nd January 2019) - Zhang, Yu; Tang, Jianguo; Wang, Yao; Liu, Jixian; Zhao, Feng; Wickramasinghe, Ranil; Belfiore, Laruence A.
ABSTRACT: In this article, the microporous membrane of stretched polytetrafluoroethylene (S-PTFE) film was modified through grafting hydrophilic methacrylic acid (MAA). SEM image showed that the grafted poly(methacrylic acid) (PMAA) covered uniquely on regular nanofiber-frame in S-PTFE. The surface contact angle of the membrane minishes rapidly with the increase of grafting ratio and falls down to the minimum point at 57° when the grafting ratio is about 4.7%. The water flux of the PTFE-g-PMAA membrane is very sensitive to pH values. At lower pH, the larger water flux was obtained. This contribution indicate the possibility of adjustable water flux by pH. GRAPHICAL ABSTRACT: